Aflatoxin M1 contamination in raw milk from major milk-producing areas of China during four seasons of 2016. (December 2017) - Li, Songli; Min, Li; Wang, Pengpeng; Zhang, Yangdong; Zheng, Nan; Wang, Jiaqi
Abstract: This survey was performed to determine the frequency with which raw milk from the major milk-producing areas of China was contaminated with aflatoxin M1 (AFM1) in 2016. In total, 5650 raw milk samples produced during the four seasons of 2016 were collected from the major milk-producing areas of China, including Hebei, Heilongjiang, Henan, Inner Mongolia, Shandong, and Xingjiang provinces. Contamination of AFM1 was detected in 267 of the 5650 raw milk samples in totally, with the incidence of 4.7%. Only 1.1% of raw milk samples exceeded the European Union legal limit (50 ng/L), and none of samples exceeded the Chinese and United States legal limit (500 ng/L). The incidence of AFM1 contamination in raw milk samples was much higher during winter (10.2%) than in spring, summer, or autumn (3.0%, 2.1%, and 4.4%, respectively) in China. Thus, it is particularly important to monitor AFM1 contamination in raw milk during the winter season. This comprehensive study will facilitate future risk analysis and the management of AFM1 contamination in raw milk in China. Highlights: Analysis of aflatoxin M1 contamination in raw milk from major milk-producing areas of China was performed. Contamination of AFM1 was detected in 267 of the 5650 raw milk samples in 2016. Only 1.1% of raw milk samples exceeded the European Union legal limit. The incidence of AFM1 contamination in raw milk was much higher during winter.